Lebron James - Gregory, Josh (New York : Bearport Publishing, 2014)
A brief biography of basketball legend LeBron James.
Just seconds left -- A shooting star -- Whiz kid -- Going pro -- A star from the start -- A move to Miami -- Hometown hero -- Back to school -- A living legend.
Includes bibliographical references (page 24) and index.
Keywords: James, LeBron -- Juvenile literature; James, LeBron; James, LeBron; Basketball players -- Biography -- United States; African American basketball players -- Biography; Basketball players -- Biography -- United States; African American basketball players -- Biography; Basketball players -- Biography -- United States; African American basketball players -- Biography